(3eSGFd aj GdCfSGH hCLhHJgGs - (3eLghds
(3ChdgG (B:s
(3eSCdI (B: (3CQHYI JfGSdh , QCh GdfHj Udi Gddg Ydjg hSde aj YUQ hGMO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B133 - (3U(B135s
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B141 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs